Single Virus Targeting Multiple Organs: What We Know and Where We Are Heading? - Prasad, Ashish; Prasad, Manoj (Frontiers in Medicine, 2020)
COVID-19 caused by SARS-CoV-2 has already infected more than 6.3 million people worldwide as on 1st June 2020 and caused a global medical emergency. Healthcare professionals have been struggling to devise appropriate therapeutic strategies against the virus mainly due to the diverse range of symptoms and multiple organ failure in infected patients. Several broad-spectrum antiviral drugs are being used for treatment however, there is yet no specific drug or vaccine against the virus. Multiple organ failure due to hyperactivity of the immune system resulting in cytokine storms is a major reason for death among the 5% critically ill patients. In this article, we have discussed the damage caused by COVID-19 on different organs of the human body.